Projeto transcritivo da Suite op. 14 de Béla Bartók para dois violões: a tradutologia como base para repensar as possibilidades instrumentais - Michel Barboza Maciel (2024)
This thesis, based on the premise that transcription practice is fundamental for expanding the guitar repertoire, especially through the adaptation of works originally written for piano, investigates musical transcription as a form of translation and explores its intersections with literary translation. It employs concepts such as fidelity, intertextuality, cultural codes, the untranslatability of poetic texts, dynamic interpretation, and creative translation, as discussed by scholars such as Susan Bassnett, Yuri Lotman, Hans-Georg Gadamer, and Haroldo de Campos. The central focus of the work is the creation of a transcription for two guitars of the Suite op.14 for piano by Hungarian composer Béla Bartók. The research includes an analysis of Bartók's biography, as well as the historical and aesthetic context that influenced the creation of the work. The transcription process is based on the interpretation and recreation of musical signs, using specific elements of the target instrumental formation in a careful and creative manner. Although these elements may diverge from the literalness of the original text, the aim is precisely to recreate these signs in the new instrumental context, re-signifying the musical expressiveness. The analysis of the transcription for two guitars of Alberto Ginastera's Sonata op.22 by Sérgio Assad served as the basis for the transcription process discussed in this work. In this analysis, we examine the genesis of the work, the influences and style of the composer, as well as the resources used by Assad to recreate expressiveness and musical signs. The thesis proposes a theoretical-practical model for musical transcription, arguing that, similar to literary translation, transcription can reveal new artistic and interpretative dimensions of the original work, enriching and diversifying the guitar repertoire. In the end, the complete transcription for two guitars of the Suite op.14 is presented, accompanied by a critical analysis that aims to consolidate the proposed theoretical approach.